Optical properties of dielectric layers with CeO₂ - Semikina, T.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The polycrystalline thin films CeO₂, WO₃, amorphous complex films WO₃ + CeO₂ with content of CeO₂ in the powder 10, 15 and 20 %, and CeO₂ + Dy₂O₃ with content of Dy₂O3 in the powder 10, 15 and 20 % are obtained by vacuum deposition method via powder evaporation. For the first time the optical characteristics of complex films WO₃ + CeO₂ and CeO₂+Dy₂O₃ are obtained. As a results of films investigation by ellipsometry the dependencies of refraction and extinction coefficients on incident beam energy are presented. The dielectric permittivity and energy band gapes are calculated. The refraction coefficients of films CeO₂ are 1.85–2.85 and are not more than 2.37 for complex films. Dielectric constant e of complex films are 3.57–4.16, and e =4.7 of CeO₂ film. The CeO₂, WO₃, and WO₃ + CeO₂ films have wide band gape Eg = 2.8–3.37 eV.